1981
DOI: 10.1007/bf01324183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiation on normal tissues: Hypothetical mechanisms and limitations of in situ assays of clonogenicity

Abstract: It is argued that proliferating normal tissues fall into two categories. In type H (for hierarchical) tissues, cells either multiply or perform tissue-specific functions. Sterilizing doses or radiation immediately initiate a gradual depopulation of irreversibly postmitotic, mature cells. The constant rate of functional cell depletion is given by physiological longevity of the cells. Consequently the onset of maximal depopulation is dose-independent and, after a range of radiation doses, the peak of milder dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(21 citation statements)
references
References 25 publications
1
19
1
Order By: Relevance
“…This is essential whenever new cells are needed during growth and regeneration and a!ords, in turn, intracellular di!erentiation signals to stop proliferation again. Examples are the endo-and mesothelium, kidney parenchyma, hepatocytes, neuroglia, CONTROL OF CELL PROLIFERATION "brocytes (Michalowski, 1981), and vascular smooth muscle cells (Owens & Wise, 1997).…”
Section: Cooperation Of the Intracellular Timer With Extracellular Simentioning
confidence: 99%
“…This is essential whenever new cells are needed during growth and regeneration and a!ords, in turn, intracellular di!erentiation signals to stop proliferation again. Examples are the endo-and mesothelium, kidney parenchyma, hepatocytes, neuroglia, CONTROL OF CELL PROLIFERATION "brocytes (Michalowski, 1981), and vascular smooth muscle cells (Owens & Wise, 1997).…”
Section: Cooperation Of the Intracellular Timer With Extracellular Simentioning
confidence: 99%
“…The mechanisms behind the early effects are rela tively well understood [8], but this is not so for the late effects. However, it has been suggested that vascular dam age is the predominant factor leading to the development of late effects.…”
Section: Discussionmentioning
confidence: 99%
“…During forthcoming embryogenesis further intermediate steps of determination and diVerentiation lead to the development of a pedigree of cell types with terminally diVerentiated cells (Slack 1991). In the adult stage of mammals the processes of cell specialization continue in the cell renewal systems that exist both as a hierarchical type that contains true stem cells, and a Xexible type that does not contain stem cells (Michalowski 1981) and thus depends on dediVerentiation for cell renewal (Fig. 1).…”
Section: The Processes Leading To Cell Specialization and Repression mentioning
confidence: 98%
“…The reason is that there are tissues the cells of which must perform specialized functions and still be able to proliferate if new cells are needed during the growth of the organism or when injured or worn cells must be replaced. In mammals this is known to occur in the so-called Xexible cell renewal systems such as in the endo-and mesothelium, liver and kidney parenchymal cells, Wbroblasts, neuroglia (Michalowski 1981), Schwann cells (Casella et al 2000) and vascular smooth muscle cells (Owens and Wise 1997). To execute specialized functions, these cells require cytoplasmic structures which are incompatible with proliferation and, thus, must be disassembled or dislocated before the cells are able to enter mitosis (Warren and Wickner 1996).…”
Section: The Necessity Of Dediverentiationmentioning
confidence: 98%